Epigenetic Remodeling in Male Germline Development - Na Li; Qiaoyan Shen; Jinlian Hua (Stem Cells International)
In mammals, germ cells guarantee the inheritance of genetic and epigenetic information across generations and are the origin of a new organism. During embryo development, the blastocyst is formed in the early stage, is comprised of an inner cell mass which is pluripotent, and could give rise to the embryonic stem cells (ESCs). The inner cell mass undergoes demethylation processes and will reestablish a methylated state that is similar to that of somatic cells later in epiblast stage. Primordial germ cells (PGCs) will be formed very soon and accompanied by the process of genome-wide demethylation. With the input of male sex determination genes, spermatogonial stem cells (SSCs) are generated and undergo the process of spermatogenesis. Spermatogenesis is a delicately regulated process in which various regulations are launched to guarantee normal mitosis and meiosis in SSCs. During all these processes, especially during spermatid development, DNA methylation profile and histone modifications are of crucial importance. In this review, we will discuss the epigenetic modifications from zygote formation to mature sperm generation and their significance to these development processes.